Organ-sparing Intensity-modulated radiotherapy for anal cancer using the ACTII schedule: a comparison of conventional and intensity-modulated radiotherapy plans. - Brooks, C; Lee, Y; Aitken, K; Hansen, V; Tait, D; Hawkins, M (2013)
AIMS: Conventional external beam radiotherapy for anal cancer is associated with a high rate of treatment-related morbidity. The purpose of this retrospective study was to compare the dosimetric advantages of three intensity-modulated radiotherapy (IMRT) plans with the conventional plan with regards to organs at risk avoidance delivering the ACTII schedule of 50.4 Gy in 1.8 Gy/fraction: 17 fractions for phase 1 and 11 fractions for phase 2. MATERIALS AND METHODS: Ten anal cancer patients (T1-3 N0-3) treated with the conventional plan using four fields and conformal boost were identified. The phase 1 planning target volume (PTV) included tumour, anal canal and inguinal, peri-rectal and internal/external iliac nodes. Phase 2 included identifiable disease only. Three step-and-shoot IMRT plans were generated: IMRT1: phase 1 inverse-planned IMRT with two- to four-field conformal phase 2; IMRT2: both phase 1 and phase 2 inverse-planned IMRT; IMRT3: phase 1 IMRT and phase 2 forward-planned IMRT. All IMRT plans were then compared against the conventional plan on PTV coverage, small bowel, genitalia, femoral heads, bladder and healthy tissue dose volume information. RESULTS: While achieving similar PTV coverage compared with the conventional plan, significant dose reductions were observed for IMRT plans in external genitalia, small bowel and healthy tissue. Reductions were also observed in the femoral heads and bladder. CONCLUSIONS: IMRT significantly reduces the dose to organs at risk while maintaining excellent PTV coverage in anal cancer radiotherapy.